Axiology of “Russian“ in the prose of Jaroslav Rudiš: Аксиология «русского» в прозе Ярослава Рудиш - Artemov, Andrej (Przegląd Wschodnioeuropejski, 2020)
The article is devoted to the assessment of the “Russian” aspect in Czech history and culture based on the prose of Jaroslav Rudiš. Jaroslav Rudiš, one of the most prominent contemporary Czech writers, was born in Turnov (1972). Since the publishing of “The Sky under Berlin” (2002), his work has positively attracted the attention of critics and has won a wider community of readers, which is evidenced by several reprints of his books and a considerable interest in the new one. Jaroslav Rudiš distinguishes himself from the other modern Czech authors by the ability to soberly, aptly and relevantly describe the problems of contemporaries. His characters are people who personally experienced the “whiff ” of the history and felt changes in Czech society over the second half of the 20th century. Despite the fact that Rudiš does not write explicitly about Russia, does not talk about the eternal themes of Russian philosophy and culture and does not discuss positive or negative aspects of Russian influence on international politics, he shows the impact of the “Russian” aspect on the course of the newest Czech history quite accurately and ironically, although infrequently. Russia and the “Russian” in the prose of the author are mentioned in connection with the events in the lives of individual heroes who perceive the Russian aspect as given and periodically interacting with their lives depending on the circumstances. The views of his characters are ambiguous: they are not strictly negative with regard to important events, but they are not thoughtlessly positive, when the breathtaking spirit and depriving rational thinking of the wonderful creative ability of the Russian soul are praised. The tonality of Rudiš’s prose is comparable to Dovlatov’s irony of the “Reserve” or to the poetry of the Yerofeyev’s “Moscow − Petushki”. The study of Rudish’s prose was carried out by the method of excerpt from the available Czech texts of the writer. Axiological characteristics (more than 120 citations from 7 works of the author) relevant for representing the image of the “Russian” in Czech literature were analyzed from the point of view of imagological criteria.the religious feeling.